WORKSHOP PROGRAM EFFORT OF COMMUNITY LEARNING CENTER (PKBM) IN PREVENTING TEENAGER PROMISCUITY (Case Study in PKBM Bina Mandiri Cipageran Cimahi) - Nunu M. Firdaus (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2018)
PKBM is an institution engaged in education and is formed by the community for people. PKBM is still under the supervision and guidance of the National Education Office. PKBM can be either in village or sub-district level. However, the establishment of this institution has not been so many yet, because the community assumption related to the need of PKBM is still low. Through this study, the researcher wants to reveal the important role of PLS as in this case is PKBM to become the vehicle of education for the community. In the current era of globalization free social relations increasingly widespread and certainly harm the dignity and dignity of the nation. So the function of the PLS as a substitute, the complement of formal education needs to be strengthened so that the education department is really able to form a complete Indonesian man. Challenges in the globalization era are very large towards the world of education, the development of science and technology changes the social life of Indonesian people, especially foreign cultures threaten the civilization of Indonesia nation. In forming complete Indonesian people, education determine direction of the next generation, through formal education, but it is not entirely successful without the supports of non-formal school or. As the negative result, promiscuity among people or even students is inevitable. In related to this problem, the researcher wants to prove that non-formal education gives effects to the development of Indonesian people generation. The researcher does comparison to the regions which have PKBM institutions in order to provide a clear picture. This study uses qualitative method to see the clear picture of PKBM effort in assessing the outcome of training program on the distribution of talents and interest of adolescents in preventing promiscuity, with the population being sampled as many as 6 people taken from studying citizens. From the results of this research, the role of PKBM training program makes teenagers social relationship become better and more beneficial. PKBM provides a lot of educational support to the community and also becomes a forum for youth and young women. It can be concluded that PKBM can prevent the teenagers from promiscuity, therefore, it is expected that PKBM is established in every village, so that formal education is equipped by non-formal Education because it gives a positive impact on the behavior of the younger generation.